Pengembangan SDM Dalam Arsitektur Bisnis Sebagai Strategi Dalam Optimasi Produktivitas Kinerja SDM - Tanni Maisari; Asti Amalia Nur Fajrillah (ISB Atma Luhur, 2020)
As time goes by the needs and aspects of competence and productivity of Human Resources (HR) are increasingly diverse to form complex communication patterns. To balance and fulfill those needs and aspects, there needs to be an increase in performance, one of them is with enterprise architecture (EA). This study raises the case of one manufacturing company with a focus on the HR management function which has problems regarding the composition and competency of HR that is uneven so that HR productivity is low. One solution to this problem is by designing an EA. The solution produced in this research is expected to be able to meet the company's business requirements which will then be able to help meet the goals of the HR management function and also the company by considering aspects of HR. The design method of this research EA uses TOGAF ADM (The Open Group Architecture Framework) which is one of the frameworks for designing EA by connecting business architecture, data, applications, and technology. TOGAF ADM is flexible so it is possible to proceed with a different framework. In this research, EA design focuses on only three stages, namely the preliminary phase, architecture vision, and business architecture. Business architecture is a phase in the TOGAF ADM which acts as the main component capable of sustaining further architecture. The business architecture contains the definition of baseline architecture and targeting which will be used as guidelines for the basis for the development of integrated information systems for the HR Management Function. Business architecture is very instrumental in helping to handle the issues and risks that occur in the company, so it can facilitate the company to make the right decision.